Development of Voicing Contrast: A Comparison of Voice Onset Time in Stop Perception - Savithri S.R; Pushpavathi M.; Sujatha V.Shastry (Journal of All India Institute of Speech and Hearing)
The study investigated development of voicing contrast in 4-7 year old Kannada speaking children. Six children each in the age range of 4-5, 5-6, and 6-7 years participated in the study. Voice onset time (VOT) continuum of /g-k/, /d -t/, and /b – p/ were synthesized. Subjects listened to the tokens and identified the stops on a binary forced-choice format. The results indicated that VOT was a strong cue in perception of voicing in Kannada.